Sosok Perempuan dalam Pandangan Bung Karno pada Memoar Sarinah: Sebuah Analisis Wacana Kritis Feminis - Suyanto Suyanto (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2019)
This study aims: (1) to describe and explain Soekarno's views about women in Sarinah’s memoir by Ir. Soekarno and (2) explained the portrait of Sarinah, a woman during the independence period. Both of these aspects are explained in the frame of sociocultural factors that cause sexism in Sarinah’s memoirs. The material object of this research is a memoir entitled Sarinah, by Ir. Soekarno, first President of the Republic of Indonesia. The formal object of this research is the use of Indonesian in the perspective of critical feminist discourse analysis in the Sara Mills Model. Data collection is done by referring to the method developed with note-taking techniques and literature studies to capture data on social identity, knowledge, and author’s beliefs and literature to obtain data on the social, institutional, and situation of the birth of the memoir. Data analysis is done by reducing data, displaying data, verifying data, interpreting and interpreting the theory, and summarizing the results. In analyzing the data of this study, it was explained by Sara Mills’s feminist stylistic theory and Teun van Dijk's social cognition theory.